The provisioning of collective goods by MNEs in emerging markets. Issue 1 (13th April 2017) - Boddewyn, Jean J.
Abstract : Purpose: This paper aims to determine the essential "collective goods" which a foreign multinational enterprise (MNE) must have before production can start in a remote area of an emerging economy, and to consider the alternative governance modes available to procure or create these goods. Design/methodology/approach: This purpose is examined conceptually and theoretically. First, the concept of "collective goods" is presented, followed by a consideration of the traditional "buy, ally or make" contractual approaches available to obtain goods and services. These approaches are repositioned in the context of an "emerging economy" so that alternative "ordering systems" as well as "non-contractual" means of obtaining things have to be considered in the context of internalization and reciprocity theories. Findings: It is difficult to obtain collective goods in remote areas of emerging economies where private ordering prevails and even succeeds but at high transaction costs and with substantial government intervention. However, the use of non-contractual modes of exchange such as reciprocity is available to facilitate exchanges between market MNEs and nonmarket state offices and civil-society associations such as non-governmental organizations with which collaboration is necessary but which cannot be acquired or controlled by MNEs. However, market firms can use philanthropy and lobbying to obtain the help of these nonmarket actors who know how to operate under private and state-ordering systems. Research limitations/implications: Theoretical implications: Internalization theory explains why MNEs are able to obtain collective goods by providing them "in-house", while reciprocity theory exemplifies how non-contractual modes of exchange can substitute for the traditional but contractual "buy, ally and/or make". Practical implications: Managerial implications: In terms of the organizational structure of the subsidiary of an MNE operating in an emerging economy, it appears that the line functions of procurement, engineering and production may rely more on contractual exchanges with foreign suppliers, while the staff functions of public affairs, government relations and human resources may be more adept at using reciprocal exchange with local suppliers. Originality/value: The provisioning of the collective goods when a firm builds its facilities in a remote and underdeveloped part of an emerging economy has hardly received any research attention nor have the non-contractual ways – such as reciprocity – available in the context of private ordering to obtain these goods.